Tren Riset Echo chambers dalam Kampanye Politik di Media Sosial: Analisis Bibliometrik Publikasi Scopus (2014-2024) - Ulaa, Abyan Daffa; Junaedi, Fajar (Universitas Muhammdiyah Yogyakarta, 2026)
This study addresses the fragmentation of prior research on echo chambers, social media, and political campaigns by providing a systematic bibliometric mapping of their intellectual structure and evolving trends. Using a bibliometric approach, this study analyzes 238 documents indexed in the Scopus database published between 2014 and 2024. The findings demonstrate a marked acceleration in publication output, particularly after 2018, reflecting the increasing centrality of digital platforms in political communication research. Geographically, the United States dominates scholarly production, followed by the United Kingdom and several European countries, indicating a concentration of knowledge production in Western contexts with limited representation from the Global South. Disciplinary analysis reveals the dominance of Social Sciences and Computer Science, underscoring the hybridization of political communication and computational approaches. Furthermore, co-occurrence network analysis identifies three major thematic clusters: (1) individual-level processes, including selective exposure and affective polarization; (2) political actors, campaign strategies, and electoral dynamics; and (3) platform-based communication, discourse, and the diffusion of misinformation. These results suggest a significant shift from early descriptive studies toward more complex, integrative, and data-driven analyses of digital political environments. This study contributes by bridging fragmented strands of literature and offering a comprehensive global overview that highlights both the consolidation of dominant research agendas and the need for more geographically diverse and theoretically integrated future research.